Elements of argumentation - Besnard, Philippe, 1958- (MIT Press, 2008)
Here the authors introduce techniques for formalizing deductive argumentation in artificial intelligence, emphasising emerging formalizations for practical argumentation. They discuss how arguments can be constructed, how key intrinsic and extrinsic factors can be identified, and how these analyses can be harnessed in the real world.
Keywords: Artificial intelligence.; Reasoning.; Logic.; Information technology.; Electronic data processing.; Intelligence artificielle.; Technologie de l'information.; artificial intelligence.; information technology.; COMPUTERS -- Enterprise Applications -- Business Intelligence Tools.; COMPUTERS -- Intelligence (AI) & Semantics.; Electronic data processing; Artificial intelligence; Information technology; Logic; Reasoning; COMPUTER SCIENCE/Artificial Intelligence